PARP inhibition in BRCA2-mutated prostate cancer - Nientiedt, Cathleen; Tolstov, Yanis; Volckmar, Anna-Lena; Endris, Volker; Haberkorn, Uwe; Jäger, Dirk; Stenzinger, Albrecht; Hohenfellner, Markus; Grüllich, Carsten; Duensing, Stefan (Annals of oncology, 2017)
Defects in DNA repair genes are increasingly recognized as a defining molecular feature of a subset of patients with prostate cancer. Poly (ADP-ribose) polymerase (PARP) inhibitors have been shown to have clinical activity in this subgroup, but other compounds including platinum also warrant exploration. We report here the remarkable clinical course of a patient with a germline BRCA2 mutation treated with the PARP inhibitor olaparib.